Center Application of General Principles of Good Governance in Government Law Decree No. 32/2008 On Administrative Procedure in Timor Leste - Manuel Pinto; Leonito Ribeiro (IHSA Institute, 2022)
In Europe, in the 18th century, generally, many countries with a formal (classical) legal ideology recognized the type of capitalistic individualist liberal state. The concept of a welfare state arises and develops, as the response of the state as a night watchman. But a welfare state can have an impact on the abuse of power. The concept of a rule of law requires the existence of both written and unwritten legal instruments that can be used as a reference in measuring government performance. And one of the benchmarks is to use the General Principles of Good Governance. In TLs, one of the government laws is the Government Law Decree No.32/2008 concerning Administrative Procedure Through this research, the author tries to explore the application of general principles of good governance in this Government Law Decree No.32/2008. The type is normative legal research, based on the law formation theory and the concept of general principles of good governance. The purpose of the study is to know and understand the position and application of the General Principles of Good Governance in the Government Law Decree Number 32/2008 concerning Public Administration Procedures in TLs. This study reveals the legal basis of the General Principles of Good Governance of several regulations. The results show that the general principle of good governance is currently regulated, normalized, and comprehensively in regulation in Timor Leste.